Gender Based Violence in Higher Education: A Model of Protection and Law Enforcement - Setiawan, Andry; Pangaribuan, Shalisha Danica; Chastine, Giovanni Helennia; Nurfebriyanti, Safa; Noviatantri, Shavia Hana (Universitas Negeri Semarang, 2023)
Gender-based violence is a phenomenon that is still encountered in academic environments, including at Semarang State University (UNNES). This study aims to analyze gender-based violence at UNNES from the point of view of international law, international conventions that have been ratified by Indonesia related to women's protection, and existing regulations and policies at UNNES related to this issue. The research method used is a juridical normative approach by collecting data through literature studies, document analysis, and interviews with related parties. The results showed that gender-based violence at UNNES includes various forms, including sexual harassment, gender discrimination, gender stereotypes, and policies that are not in favor of women. This research also revealed that UNNES has adopted several regulations and policies related to gender issues, but there is still a gap between existing policies and their implementation. In addition, international conventions that have been ratified by Indonesia are also an important basis in protecting women from gender-based violence in the academic environment. This research provides recommendations to UNNES to strengthen the implementation of existing regulations and policies related to gender issues, as well as increase awareness and understanding of gender-based violence to the entire UNNES academic community. In addition, this research is also expected to be a reference for researchers and policy makers in dealing with the issue of gender-based violence in the university environment and encourage the adoption of policies that favor the protection of women's rights.